Mental illness and suicide among physicians. Issue 10303 (4th September 2021) - Harvey, Samuel B; Epstein, Ronald M; Glozier, Nicholas; Petrie, Katherine; Strudwick, Jessica; Gayed, Aimee; Dean, Kimberlie; Henderson, Max
Summary: The COVID-19 pandemic has heightened interest in how physician mental health can be protected and optimised, but uncertainty and misinformation remain about some key issues. In this Review, we discuss the current literature, which shows that despite what might be inferred during training, physicians are not immune to mental illness, with between a quarter and a third reporting increased symptoms of mental ill health. Physicians, particularly female physicians, are at an increased risk of suicide. An emerging consensus exists that some aspects of physician training, working conditions, and organisational support are unacceptable. Changes in medical training and health systems, and the additional strain of working through a pandemic, might have amplified these problems. A new evidence-informed framework for how individual and organisational interventions can be used in an integrated manner in medical schools, in health-care settings, and by professional colleagues is proposed. New initiatives are required at each of these levels, with an urgent need for organisational-level interventions, to better protect the mental health and wellbeing of physicians.